Peran Teman Sebaya Terhadap Perilaku Seksual Pranikah Pada Remaja Di Lingkungan Sekolah Menengah Kejuruan Y Di Pacitan - Pradhana, Dimas, Winarsih Nur A., S.Kep., Ns., Etn., M.Kep (2016)
In adolescence, a child has a biological maturity, and characteristics that adolescents have a curiosity so great, love adventure and challenges as well as tend to dare to risk without any prior careful thought, including against and premarital sexual behavior. Teens who had premarital sexual behavior may be motivated by several factors such as the role of parents, the media, gadgets, and the influence of the attitudes and behavior of peers. This study aimed to determine the attitudes of peers toward premarital sexual behavior in adolescents in the Vocational High School Y in Pacitan in 2016. This study is a quantitative study with descriptive correlation with cross sectional approach. The study population was all students / senior high school Y students in Pacitan, was of 4734 students, while the samples are 120 respondents by purposive sampling technique. Collecting data using a questionnaire and analyzed using Chi Square test. The result of Chi Square test analysis attitude peer relationships with adolescent sexual behavior obtained 2obs value of 28.054 (p-value = 0.000), thus rejecting H0. The conclusion of research there was a relationship attitudes of peers with premarital sexual behavior in students in vocational environment in Pacitan in 2016, the respondents who have a positive attitude has a tendency not conduct premarital sexual behavior.